MODERN FORMS OF FOREIGN LANGUAGES LEARNING AND TEACHING (Лучшие интеллектуальные исследования, 2025)
Annotation: English pronunciation exhibits considerable diversity, influenced by geographical, social, and contextual factors. This article explores the primary types of English pronunciation and delves into the status of Received Pronunciation (RP) within this spectrum.